2017
DOI: 10.1097/md.0000000000007800
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of preference and efficacy of adalimumab and infliximab for treating ulcerative colitis naive to antitumor necrosis factor therapy

Abstract: There have been few reports on 2 tumor necrosis factor alpha inhibitors, infliximab and adalimumab, with respect to patient preference and efficacy in ulcerative colitis (UC).We used questionnaires to evaluate the preference and reasons for drug choice between infliximab and adalimumab in UC patients naive to antitumor necrosis factor alpha therapy. We also analyzed the efficacy of infliximab and adalimumab prospectively and endoscopically before treatment and at 14 and 54 weeks.Of the 25 UC patients, inflixim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Furthermore, as our study was conducted in reallife setting, assessment of clinical response might have been less stringent compared to a placebo-controlled trial and a prospective study from Japan. 8,9,19 Partial Mayo score after 8 weeks of adalimumab therapy was found to be associated with discontinuing maintenance therapy in our study. Likewise, a previous Spanish study reported that a lack of response at week 12 was associated with an increased probability of discontinuing adalimumab and a higher rate of colectomy.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Furthermore, as our study was conducted in reallife setting, assessment of clinical response might have been less stringent compared to a placebo-controlled trial and a prospective study from Japan. 8,9,19 Partial Mayo score after 8 weeks of adalimumab therapy was found to be associated with discontinuing maintenance therapy in our study. Likewise, a previous Spanish study reported that a lack of response at week 12 was associated with an increased probability of discontinuing adalimumab and a higher rate of colectomy.…”
Section: Discussionmentioning
confidence: 47%
“…8,9 In another prospective study from Japan, 73.3% of UC patients responded to adalimumab therapy at week 14 in 15 anti-TNF-naïve UC patients. 19 Furthermore, the drop-out rate before week 54 was 40% (6/15) and the response, remission, and mucosal healing rates at week 54 were 66.7%, 53.3%, and 58.3%, respectively. 19 In our study, 92% of patients entered into adalimumab maintenance therapy and the cumulative rate of maintaining adalimumab therapy until 1 year was 70.0% among the patients who received adalimumab therapy for 8 weeks or more.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Considering the data for the IFX and ADA subgroups, we did not see any differences in overall efficiency in 8 weeks. Mizoshita et al 31 showed that the efficacy of ADA in remission induction was also equivalent to that of IFX in UC patients who had not previously used anti-TNF agents. Contrarily, a recent indirect comparison meta-analysis 32 and network meta-analysis 33,34 showed that IFX is superior to ADA in the induction of remission in UC patients.…”
Section: Discussionmentioning
confidence: 99%